2015
DOI: 10.5935/1414-8145.20150089
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of homophobia on adolescent health

Abstract: Objective: This study had the purpose of recognizing the types of violence suffered by homosexual adolescents and understanding the effects of homophobia on the health of this group. Methods: In-depth interviews were conducted with nine adolescents that live in a country town on the state of São Paulo who declared themselves homosexuals. Results: The respondents reported cases of physical, verbal, psychological and sexual violence. Homophobia causes negative perceptions about themselves and the non-adoption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
0
7
0
4
Order By: Relevance
“…A homofobia internalizada está relacionada a desfechos negativos de saúde mental, funcionando como fator de risco para esse grupo minoritário, inclusive no que tange a autoestima, fragilização do autocuidado e comportamentos de risco, como suicídio (Blais, Gervais, & Hébert, 2014;Montoya, Loyo, Correa-Márquez, & Flores, 2015;Natarelli, Braga, Oliveira, & Silva, 2015). A homofobia internalizada pode afetar homossexuais e bissexuais de diversas formas: diminuindo a satisfação conjugal, aumentando ideação e tentativas de suicídio, aumentando risco de abuso de substâncias, aumentando risco de desfechos negativos de saúde mental (como ansiedade e depressão), aumentando a chance de desfechos psicológicos negativos (como isolamento social, preconceito, supercompensação, supressão de sentimentos, confusão emocional, etc.)…”
Section: Discussionunclassified
“…A homofobia internalizada está relacionada a desfechos negativos de saúde mental, funcionando como fator de risco para esse grupo minoritário, inclusive no que tange a autoestima, fragilização do autocuidado e comportamentos de risco, como suicídio (Blais, Gervais, & Hébert, 2014;Montoya, Loyo, Correa-Márquez, & Flores, 2015;Natarelli, Braga, Oliveira, & Silva, 2015). A homofobia internalizada pode afetar homossexuais e bissexuais de diversas formas: diminuindo a satisfação conjugal, aumentando ideação e tentativas de suicídio, aumentando risco de abuso de substâncias, aumentando risco de desfechos negativos de saúde mental (como ansiedade e depressão), aumentando a chance de desfechos psicológicos negativos (como isolamento social, preconceito, supercompensação, supressão de sentimentos, confusão emocional, etc.)…”
Section: Discussionunclassified
“…Many families, faced with the dissidence of the heterosexuality of their members, carry out a series of punishments, ranging from mild verbal offenses to serious physical violence (24) . Studies show that rejection and family violence in the outcoming process and the non-provision of social support have a direct impact on the health of homosexual adolescents and young people, with consequences such as: social isolation, depression, suicidal ideation and attempt, low performance low self-esteem, higher social exposures and an increase in internalized homophobia (1)(2)(25)(26) . Data from a survey of ten women living heterosexual-normative dissenting lifestyles with a focus on homophobia in the family context revealed that families exert control over their members in order to maintain the compulsion of heterosexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Além da culpa, vergonha e medo, o participante 3 relata uma violência sexual sistemática em sua adolescência. Esses estressores e seus sinais de impacto na saúde se assemelham a outros estudos no Brasil (Natarelli, Braga, Oliveira, & Silva, 2015) e no exterior (Almeida, Johnson, Corliss, Molnar & Azrael, 2009;Saewyc, 2011), que endossam a manutenção da vulnerabilidade por conta da homofobia.…”
Section: Rafael Zanata Albertini Márcio Luís Costa E Rodrigo Lopes Munclassified